(untitled) (Al-Qamar, 2021)
This investigation intends to discuss the disadvantages and miseries of floods especially in Pakistan and the strategies about protection according to modern and Islamic teachings in this regard. Water is a great blessing of Allah Almighty, but the strange thing is that if water becomes less, human life becomes difficult and if there is too much water, human life is also seriously threatened. In this context, it is very important to have a balance so that human life is not exposed to dangers. In this chapter, the issues and problems related to floods will be discussed in the Islamic context and the teachings of Shariah will be clarified in the context of flood prevention. Pakistan is an agricultural country which has the best and longest canal system in the world, due to which a network of canals is widely spread across the country and if a flood situation occurs in the country, a large area of ​​the country will be affected especially most areas of southern Punjab and Sindh, so it is very important that every possible effort is made to save them from the destruction of floods and no delay should be taken. In this regard, people should be protected with the help of modern technology and equipment, best strategies and procedures and a team of active and sincere people who have received the best training in flood prevention. This article mentions the same things.